The Effect Of Giving Acupressure Therapy On Increasing Appetite In Children Aged 1-5 Years At PMB Mutiara/N.Purba Medan Sunggal In 2022 - Helma Liana Riska; Elvina Sari Sinaga; Herbita Suriani; Hotna Siagian; Gustri Afriany (Sean Institute, 2023)
Based on the results of the 2018 Basic Health Research (Riskesdas), under-fives were stunted at 30.8%, in 2019 it fell to 27.7%, but it is still below the 2024 national target of 14%. The number of toddlers in Indonesia who experience malnutrition is 3.9% and those who suffer from malnutrition are 13.8%. According to the health profile in Indonesia in 2020, toddlers 0-59 months are very short, 11.5%, while toddlers are short, 19.3%. The percentage of toddlers aged 0-59 months with very underweight is 3.9%, while the percentage of underweight is 13.8%. The research objective was to determine the effectiveness of acupressure on increasing appetite in children aged 1-5 years at PMB Mutiara/N.Purba Medan Sunggal. The research method used was an experiment with a one group pretest-posttest design. The entire population was used as a sample of 8 respondents. The research was conducted for 2 months. The survey found that the majority of respondents who were 2 years old were 3 people, the sexes of men and women had the same number, namely 4 people each, that of the 8 respondents who were given acupressure therapy the majority of their weight increased, namely as many as 7 people. the results of the paired t-test obtained a p-value <0.05, which is equal to 0.003, Shiatsu therapy is effective in increasing appetite in children aged 1-5 years